2021
DOI: 10.1002/jmv.27316
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity after two doses of inactivated virus vaccine in healthcare workers with and without previous COVID‐19 infection: Prospective observational study

Abstract: Vaccines have been seen as the most important solution for ending the coronavirus disease 2019 (COVID‐19) pandemic. The aim of this study is to evaluate the antibody levels after inactivated virus vaccination. We included 148 healthcare workers (74 with prior COVID‐19 infection and 74 with not). They received two doses of inactivated virus vaccine (CoronaVac). Serum samples were prospectively collected three times (Days 0, 28, 56). We measured SARS‐CoV‐2 IgGsp antibodies quantitatively and neutralizing antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
7
25
1
Order By: Relevance
“…Different results have been reported regarding the relationship between sex and vaccine response. Although a lower antibody response is frequently reported in males receiving the mRNA BNT162b2 15 , 18 or CoronaVac vaccine, 19 no difference was found between the first month antibody levels in males and females, and there was no association between male sex and low antibody levels in this study. In the univariate logistic regression analysis, nurses and other healthcare professionals were in the risk group for low antibody response compared to the physician group, but no difference was found between the occupational groups in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Different results have been reported regarding the relationship between sex and vaccine response. Although a lower antibody response is frequently reported in males receiving the mRNA BNT162b2 15 , 18 or CoronaVac vaccine, 19 no difference was found between the first month antibody levels in males and females, and there was no association between male sex and low antibody levels in this study. In the univariate logistic regression analysis, nurses and other healthcare professionals were in the risk group for low antibody response compared to the physician group, but no difference was found between the occupational groups in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 77%
“…Chronic diseases may also cause a low response to COVID‐19 vaccines, but the results of inactivated vaccine studies on this subject are quite different from each other. 14 , 19 Differences could be due to the type of chronic diseases in the study groups. Obesity is another issue that affects the response to the vaccine, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies reported that waning NAb titres have been associated with IgG anti-RBD immune response 29,30 and neutralizing capacity was positively correlated with IgG antibody titres. 31 Furthermore, the loss of short-lived plasma cells has been considered the cause of initial rapid waning of antibodies in SARS-CoV-2 infected individuals in general, while establishment of long-lived plasma was thought to contribute to the elevation of antibody level. 32,33 Defective Bcl6+ follicular T-cells due to the absence of germinal centers in the thoracic lymph nodes in dead COVID-19 patients was proposedly unable to activate memory B-cells, leading to a decrease in long-lasting and high-affinity antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Tarke et al, 2022 (USA) [29] Cross Yalçın et al, 2022 (Turkey) [30] Prospective observational study among healthcare workers (n = 148)…”
Section: Yesmentioning
confidence: 99%